ANALISIS YURIDIS PEMBANGUNAN INFRASTRUKTUR PERDESAAN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA PETIR KECAMATAN PURWANEGARA KABUPATEN BANJARNEGARA - Setianingsih, Susi; Indriati Amarini (Collegium Studiosum Journal, 2023)
This research is titled "Juridical Analysis of Rural Infrastructure Development in Improving the Welfare of the Community in Petir Village, Purwanegara Subdistrict, Banjarnegara Regency." The aim of this research is to analyze the role of the village government in rural infrastructure development and identify the factors influencing development in Petir Village. The research method employed is a normative juridical legal research with a literature study approach. Data analysis is conducted qualitatively, referring to Law Number 6 of 2014 concerning Villages and the 1945 Constitution of the Republic of Indonesia. The results of the research indicate that, in accordance with Law Number 6 of 2014, the village government has the primary responsibility for implementing development in its area. The infrastructure development program in Petir Village focuses on concrete paving, road casting, asphalt road construction, and drainage, selected through village deliberations. Despite ongoing development, there are still challenges such as unsupportive road terrain, the remote location of the village, and weather uncertainty affecting the smooth progress of development. Supporting factors for rural infrastructure development involve the participation and active involvement of the Petir Village community in every stage of development. Meanwhile, inhibiting factors include geographic constraints and weather conditions that force development delays. This research provides a comprehensive overview of the efforts of the village government in addressing national development disparities through rural infrastructure development. The implications of the research findings can serve as a basis for policy improvement and development strategy at the village level, particularly in Petir Village, to enhance community welfare.